Efeito da Cecropia pachystachya na inflamação e no estresse oxidativo na úlcera gástrica induzida por naproxeno em camundongos - Martins, Dainesy Santos (2017)
Peptic ulcer (UP) is a gastrointestinal disease in which acute and chronic inflammation of the stomach occurs, as well as duodenum, which can lead to abdominal pain, nausea, vomiting and other symptoms. UP is multifactorial by Helicobacter pylori, use of non-steroidal anti-inflammatory drugs, alcohol, smoking and cancer treatment, resulting in an imbalance between the defensive and harmful factors. Cecropia pachystachya (CP) contains flavonoids, terpenes and polyphenols, such as: the chlorogenic acid known for its antioxidant properties. The present project investigated how explanations and antiulcerogenic properties of the leaf extract ethanolic extract of CP in gastric ulcer induced by naproxen (NPX). Male Swiss mice were pretreated with carboxymethylcellulose (0.5% vc CMC) and / or CP [1], [3], [10] and [30] mg / kg. After 30 minutes, they received NPX (300 mg / kg) animals were euthanized 6 hours after the experimental protocol. Microscopes, GSH, MDA, MPO, nitrite / nitrate, TNF-a and IL-6. The stomach segments were collected for analysis. Intestinal epithelial cells (IEC-6) were used to measure cell viability by the MTT test. The macroscopic test was performed by gas evaluation planning, a microscopy using a scoring system to define how edema, loss of cell architecture, hemorrhage and cell infiltration. Tests such as GSH and MDA were performed to evaluate oxidative stress. MPO, IL-6 and TNF-α analyzed CP antiinflammatory products. The MTT result showed that the CP extract was not different from the control with the culture medium in IEC-6. CP extract significantly reduced the macroscopic and microscopic gastric lesion induced by NPX. Cecropia pachystachya at 3.0 mg / kg prevented depletion at GSH concentrations, reduced as MDA concentrations and reduced neutrophil infiltration. The extract Cecropia pachystachya reduced as concentrations of the proinflammatory cytokines TNF-α and IL-6 and reversed the effect of NPX on nitrite / nitrate. On the other hand, CP demonstrates an anti-inflammatory and antioxidant effect without a model of gastric ulcer induced by NPX. This is the first work that shows the gastroprotection of this natural product.